Conducting service research that matters. Issue 6 (14th September 2015) - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K.; McColl-Kennedy, Janet R.; Sirianni, Nancy J.; Witell, Lars; Wuenderlich, Nancy V.
Abstract : Purpose: – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach: – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings: – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value: – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.